Synergistic relationship between green finance and industrial structure upgrade in the yangtze river economic belt - Yuan, Minglan; Shi, Zetai; Tang, Decai; Zhu, Jie; Li, Jiannan (Frontiers in Environmental Science, 2024)
The Yangtze River Economic Belt (YREB) is experiencing rapid economic development, while ecological and environmental problems are prominent. The development of green finance can help optimize the upgrade of regional industrial structure and promote the improvement of the ecological environment. This study constructs an evaluation system for the development level of the YREB based on the panel data of 11 provinces (cities) in the YREB from 2010 to 2020. The entropy method is used to evaluate and analyze the current status of the ecosystem in the YREB, and a panel data model is used to conduct an in-depth investigation to explore the impact of green finance (GF) on the industrial structure upgrade (INS) of the YREB.The results of the study show that from 2010 to 2020, the level of GF development in the YREB has increased, and the INS has further developed. In addition, the growth of GF injects a strong impetus to the improvement of INS in YREB, but there are regional differences, which are more obvious in the eastern region and not significant in other regions. Finally, based on the research conclusions, relevant strategies and suggestions are proposed to assist the development of GF and INS in the YREB.